2014
DOI: 10.1124/dmd.113.056218
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of 3-n-Butylphthalide via Sulfation of Its Major Metabolite 3-Hydroxy-NBP: Mediated Mainly by Sulfotransferase 1A1

Abstract: 3-n-Butylphthalide (NBP) [(6)-3-butyl-1(3H)-isobenzofuranone] is an anti-cerebral-ischemia drug. Moderate hepatotoxicity has been observed in clinical applications. One of the major metabolites, 3-N-acetylcysteine-NBP, has been detected in human urine, indicating the formation of a reactive metabolite. We elucidated the formation mechanism of the reactive metabolite and its association with the hepatotoxicity of NBP. The in vitro incubations revealed that 3-glutathione-NBP (3-GSH-NBP) was observed only in fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Additionally, it has been found that the likelihood of drug-to-drug interaction is minimized by the diversity of enzymes, such as P450, alcohol dehydrogenase (ADH), and aldehyde dehydrogenase (ALDH), involved in its metabolism [6]. However, the participation of 3-hydroxy-NBP sulfate, one of the sulfated metabolites of dl-NBP in the process, is believed to be the main reason for dl-NBP's side effect (mild hepatotoxicity) [7]. Many researches involving stroke animal models have also concluded that NBP, through multiple mechanisms, significantly reduces the cerebral infarct size and oxidative damage, inhibits platelet aggregation, improves blood flow and mitochondrial functions, possesses antithrombotic and anti-inflammatory effects, and reduces neural apoptosis [810], hence the importance of understanding its mechanisms and the value it might hold for future management of ischemic stroke as well as neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been found that the likelihood of drug-to-drug interaction is minimized by the diversity of enzymes, such as P450, alcohol dehydrogenase (ADH), and aldehyde dehydrogenase (ALDH), involved in its metabolism [6]. However, the participation of 3-hydroxy-NBP sulfate, one of the sulfated metabolites of dl-NBP in the process, is believed to be the main reason for dl-NBP's side effect (mild hepatotoxicity) [7]. Many researches involving stroke animal models have also concluded that NBP, through multiple mechanisms, significantly reduces the cerebral infarct size and oxidative damage, inhibits platelet aggregation, improves blood flow and mitochondrial functions, possesses antithrombotic and anti-inflammatory effects, and reduces neural apoptosis [810], hence the importance of understanding its mechanisms and the value it might hold for future management of ischemic stroke as well as neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Human hepatocytes were selected, rather than human liver microsomes (HLM), to better simulate a physiological liver environment (20,21). The hepatocyte incubation model was successful in our previous studies for identifying appropriate markers for AB-FUBINACA (19), AB-PINACA (22), and AH-7921 (23), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Human hepatocytes were chosen over human liver microsomes (HLMs) because hepatocytes contain all endogenous drug-metabolizing enzymes and essential cofactors (18 ). Metabolites identified with human hepatocytes can serve as useful markers for identifying novel SCs (19 ).…”
mentioning
confidence: 99%